FORMULASI OPTIMAL MINUMAN BUBUK INSTAN JAHE MERAH–DAUN KELOR DENGAN PENAMBAHAN MALTODEKSTRIN - Marlina, Lusi; Rafiudin, Jadid (Jurnal TEDC; Vol 19 No 3 (2025): JURNAL TEDCDO - 10.70428/tedc.v19i3.1387, 2025)
Instant powdered beverages are characterized by low moisture content, allowing long shelf life and easy solubility. This study aimed to determine the optimal formulation of instant powder made from red ginger and moringa leaves with different ratios (55%:45%; 65%:35%; 75%:25%; 85%:15%) and maltodextrin levels (5–20%), processed using oven drying and a Completely Randomized Design (CRD). Organoleptic analysis was performed using Tests of Between-Subjects Effects followed by Duncan’s Multiple Range Test. Results showed that maltodextrin variation had no significant effect on moisture content, pH, vitamin C, and shelf life, but significantly influenced sensory attributes such as taste, aroma, viscosity, and the color of both powder and infusion. The best treatment was obtained from the formulation of 75% red ginger : 25% moringa with 20% maltodextrin, producing a product with favorable taste, moderately thick texture, fairly preferred aroma, and cream-yellowish color. Storage is recommended in aluminum foil packaging under dry room conditions (±27℃).